Reforma a la ley orgánica de discapacidades, en lo referente a la accesibilidad comunicacional de las personas con discapacidad auditiva en los gobiernos autónomos descentralizados - Rossana Magdalena Pincay Mera (2015)
This research arises from the need to seek analytical work of legal worth that benefits people with hearing disabilities at all times has lived immersed in a limiting their needs world because information and communication is poor because even though it is recognized the Ecuadorian sign language as the language of the deaf, little has been done; in modern times is socialized barriers or constraints to which they are exposed people with disabilities and architectural barriers, social environment, communication barriers that limit the accessibility of public services to be more effectively reach the focus sectors, to be put into effect as mandated by the Constitution of the Republic of Ecuador and the Organic Law on Disabilities Art. 70 in the second paragraph says interpreter services Ecuadorian sign language progressively incorporated in public institutions and the training of public servants and. However, two years of knowing the law and what is the reality they have gone about executing these actions anything because the problem is that even if there is determined the national system of comprehensive protection of disabled people on three levels, where are the GAD as executing agencies. No viable achieved appropriate action to develop and implement projects and programs that benefit this group of people to use a different form of communication through signs expressed their hands, known as sign language, so it is imperative to reform Art. 63 of the Organic Law on Disabilities in a paragraph to refer to communications accessibility where it is believed in the GAD department communication accessibility take charge of aid interpretation for people with disabilities add auditory and training of Ecuadorian society in sign language. It is time to let go of the past to achieve what is mentioned regain our dignity through execute what the Law commands and promote a more humane society, because we have a Constitution of the Republic of Ecuador a new form of peaceful coexistence, to achieve the good life, sumak kawsay; We investigated doctrines of eminent writers on the issue of the hearing impaired, which have coincided with the proposal set out in this, comparisons were performed with laws of other countries such as Uruguay and concluded that these are similar, we analyzed carefully what they say the human rights of persons with disabilities where the recognition, acceptance and use of sign language as the language of deaf people and understand that the attitude of the social environment is as hard as to what is must confront people with this disability, and many times unconsciously looks at them with a plaintive pain that must be eradicated because it is simply another way of life with a different routine communication this is the new paradigm must disclose to achieving a society with knowledge on this subject